Ð¢ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ð°Ñ Ð·Ð°Ð²Ð¸ÑÐ¸Ð¼Ð¾ÑÑ‚ÑŒ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ð¸ Ð½ÐµÐ¹Ñ€Ð°Ð¼Ð¸Ð½Ð¸Ð´Ð°Ð·Ñ‹ Ð²Ð¸Ñ€ÑƒÑÐ¾Ð² Ð³Ñ€Ð¸Ð¿Ð¿Ð° Ð¿Ñ‚Ð¸Ñ† Ð¸ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Gisina, I. L.; Perskiy, E. E. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The research deals with a comparative study of temperature dependencies of neuraminidase activity of birds influenza viruses, which were obtained in Israel during epizootic 2000-2004, reference strain of birds influenza viruses and two reference stains of human influenza. It was shown that temperature optimum of neuraminidase activity of chronologically later groups of birds influenza viruses approached to the activity optimum of reference strains of human influenza viruses. This confirms the hypothesis about probable transfer of avian influenza viruses to a human and vice versa, which is one of this virus evolution ways.